1997
DOI: 10.1177/002215549704500508
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Collagenase Stimulatory Factor (TCSF) Expression and Localization in Human Lung and Breast Cancers

Abstract: SUMMARYTumor cell-derived collagenase stimulatory factor (TCSF) stimulates in vitro the biosynthesis of various matrix metalloproteinases involved in tumor invasion, such as interstitial collagenase, gelatinase A, and stromelysin 1. The expression of TCSF mRNAs was studied in vivo, using in situ hybridization and Northern blotting analysis, in seven normal tissues and in 22 squamous cell carcinomas of the lung, and in seven benign proliferations and in 22 ductal carcinomas of the mammary gland. By in situ hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 25 publications
5
97
1
Order By: Relevance
“…It would be difficult, however, to clearly demonstrate regulation of the expression and activity of MMPs by EMMPRIN. Previous studies have shown that EMMPRIN stimulates fibroblasts to produce 3-10 times the usual level of MMP-1 and MMP-3 in tumor cells and Chinese hamster ovary cells (20)(21)(22). The present study showed a 1.5-3 times increase in the production of MMP-1 and MMP-3.…”
Section: Discussionsupporting
confidence: 67%
“…It would be difficult, however, to clearly demonstrate regulation of the expression and activity of MMPs by EMMPRIN. Previous studies have shown that EMMPRIN stimulates fibroblasts to produce 3-10 times the usual level of MMP-1 and MMP-3 in tumor cells and Chinese hamster ovary cells (20)(21)(22). The present study showed a 1.5-3 times increase in the production of MMP-1 and MMP-3.…”
Section: Discussionsupporting
confidence: 67%
“…4 CD147 is more highly expressed on the surface of most human carcinoma cells compared to their normal counterparts and correlates with tumor progression and invasion by stimulating peritumoral fibroblasts to produce elevated levels of several MMPs. 4,[11][12][13][14][15][16] These results imply that a CD147 counterreceptor might exist on the surface of fibroblasts, but none has been identified. Using CD147-transfected COS cells and immobilized recombinant CD147-Fc fusion protein, it was revealed that CD147 engages in a homophilic interaction, providing evidence that CD147 may be a counterreceptor for itself.…”
Section: Discussionmentioning
confidence: 99%
“…4,11 Expression of EMMPRIN is enhanced in a variety of human carcinomas and correlates with tumor progression and invasion by inducing production of MMPs by stromal cells. 4,[11][12][13][14][15][16] It was also shown in vitro that recombinant EMMPRIN purified from Chinese hamster ovary cells transfected with cDNA for human EMMPRIN stimulates cultured human fibroblasts to produce MMP-1, MMP-2 and MMP-3. 17 EMMPRIN not only stimulates the production of interstitial collagenase (MMP-1) but also forms a complex with MMP-1 at the human lung carcinoma cell surface, which would facilitate invasive processes.…”
Section: Abstract: Basigin (Cd147); Malignant Melanoma; Invasion; Mementioning
confidence: 99%
“…In turn, the expression of matrix proteinases becomes regulated by tumor cells. For example, the extracellular matrix metalloproteinase inducer (EMM-PRIN) (Biswas et al, 1995) is an intrinsic plasma membrane glycoprotein produced at high levels by cancer cells (Polette et al, 1997), which stimulates adjacent stromal cells to synthesize matrix MMPs (Guo et al, 2000).…”
Section: Enzymesmentioning
confidence: 99%